Existence and Convergence Theorems for Global Minimization of Best Proximity Points in Hilbert Spaces - Raweerote Suparatulatorn (2019)
© 2019, Springer Nature B.V. In order to solve global minimization problems involving best proximity points, we introduce general Mann algorithm for nonself nonexpansive mappings and then prove weak and strong convergence of the proposed algorithm under some suitable conditions in real Hilbert spaces. Furthermore, we also provide numerical experiment to illustrate the convergence behavior of our proposed algorithm.